Combined analysis of 16S rRNA gene sequencing data reveals core vaginal bacteria across livestock species - Jonas, Lucille C.; Youngs, Curtis R.; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2025)
Investigating the livestock vaginal microbiota is of increasing interest due to its relationship with animal reproductive performance. Recent publications have uncovered a high degree of variability of the livestock vaginal microbiota, making it difficult to focus functional research on individual microorganisms. To address this variability, we conducted a combined analysis of publicly available 16S rRNA gene amplicon sequencing datasets to reveal the core vaginal microbiota in cattle, sheep, and pigs. The goal of this combined analysis was to identify bacterial genera that were shared despite a diverse overall sample population. A total of 2,911 vaginal samples (715 cattle, 964 sheep, and 1,232 pigs) from 29 different datasets were used in this combined analysis. Beta diversity analysis revealed structural differences of the vaginal microbiota between different animal species. Compositionally, the most abundant phyla were Bacillota, Pseudomonadota, and Bacteroidota. At the genus level, an unclassified Pasteurellaceae genus, Ureaplasma, and Streptococcus were the most abundant. Across the vaginal microbiota of individual livestock species, compositional differences were observed. The cattle and sheep vaginal microbiota contained a higher abundance of Ureaplasma and Histophilus whereas the pig vaginal microbiota contained more Fusobacterium and Parvimonas than that of the other livestock samples. Among the cattle, 120 OTUs and 82 genera were present in 70% of the vaginal samples. At the same threshold, pig samples had 40 core OTUs and 63 core genera, while the sheep samples had 22 core OTUs and 50 core genera. There were 19 overlapping core vaginal genera across the three animal species. The core vaginal OTUs were largely species-specific, although there were eight overlapping OTUs. These included Streptococcus (OTU 21), Clostridium sensu stricto 1 (OTU 18), and Corynebacterium (OTU 6), which were also some of the most abundant members of the livestock core vaginal microbiota. A better understanding of the livestock vaginal microbiota is required for future studies aimed at elucidation of the functional significance of individual microbes with respect to livestock reproductive efficiency. The core vaginal genera identified in this analysis will help guide research on mechanisms/pathways through which individual organisms enhance or impede animal reproductive efficiency.